Leisure inequality in the United States: 1965 - 2003 - Almudena Sevilla; J. Ignacio Gimenez-Nadal; Jonathan I. Gershuny (Institute for the Study of Labor (IZA), 2012)
This paper exploits the complex sequential structure of the diary data in the American Heritage Time Use Study (AHTUS) and constructs three classes of indicators that capture the quality of leisure ('pure leisure', 'co-present leisure' and 'leisure fragmentation') to show that the relative growth in leisure time enjoyed by less-educated individuals documented in previous studies has been accompanied by a relative decrease in the quality of that leisure time. These results are not driven by any single leisure activity, such as time watching television. Our findings may offer a more comprehensive picture of inequality in the US and provide a basis for weighing the relative decline in earnings and consumption for the less educated against the simultaneous relative growth of leisure.
Keywords: C13; C23; D13; J12; J16; Z13; 330; leisure; inequality; income; wages; consumption; time-use; happiness; Freizeit; Soziale Ungleichheit; Zeitverwendung; USA